Long-term outcomes after catheter-ablation of atrioventricular nodal reentrant tachycardia: A ten-year follow-up - Kocijančić, Aleksandar; Simić, Dragan; Mujović, Nebojša; Potpara, Tatjana; Kovačević, Vladan; Marinković, Milan; Marić-Kocijančić, Jelena; Kocijančić Belović, Dušica (Vojnosanitetski pregled, 2021)
Background/Aim. Atrioventricular nodal (AV) reentry tachycardia (AVNRT) is the most common form of supraventricular tachycardia. Treatment of choice is a catheter-ablation of the slow pathway of the AV node. The aim of the study was to present the outcomes of this procedure after ten years of follow-up. Methods. The catheter-ablation procedure was performed in 92 patients (30 men and 62 women, mean age 52.0 ± 13.3 years, range 19 to 76 years) with confirmed AVNRT during the electrophysiological examination, from 2007 to 2009. Out of these, 64 patients were followed-up for ten years by inviting them to clinical examinations regularly. The occurrence of AV block, arrhythmia and the use of antyarrhythmic drugs were the main outcomes of the ten-year follow-up. Multivariate logistic regression was applied to identify significant predictors of arrhythmia after a follow-up period. Results. The primary success of intervention was achieved in 91 (98.9%) patients. Third-degree AV block was registered in 1 (1.1%) patient after the intervention, which required the implantation of a pacemaker. After ten years of follow-up, AVNRT relapses were not registered. A total of 7 out of 64 (10.9%) patients died during the follow-up period, mostly due to non-cardiac causes. After ten years of follow-up, first-degree AV block was registered in six (10.5%) patients, whereas other arrhythmias were observed in 17 (29.8%) patients such as atrial fibrillation or flutter, atrial premature beats and sinus tachycardia. The number of antiarrhythmic drugs were reduced from 2.1 ± 1.2 at baseline to 0.5 ± 0.6 during follow-up, mostly beta-blockers, propafenone and amiodarone, and 33 (57.9%) patients were no longer using anti-arrhythmic therapy. Logistic regression identified participant’s age above 55 years at baseline and re-intervention performed after the initial catheter-ablation as significant predictors of arrhythmia after a 10-year follow-up, independent from gender and arterial hypertension at baseline. Conclusion. The catheter-ablation of AVNRT represents a successful and safe procedure, from the perspective of ten-year follow-up.